2002 - Digital Television in the United Kingdom - Collins, Richard (Javnost-The Public, 2002)
The author describes the extent to which digital television has penetrated the UK, claimed to be Europe's leading digital television market. He argues that digitalisation of television is driven by two high level Government objectives, efficiency in radio spectrum use and promotion of online connectivity. Reference to survey research suggests considerable delay in achieving the Government's target of digital switchover by 2010. The author considers the role of the BBC, the Government's principal instrument for achieving its digital policies, and argues that there is evidence to suggest the effect of the BBC's digital services is to reduce competition and diversity. This argument is supported by data drawn from interviews with executives of competing digital channels. The author concludes by considering the likely effect of the Government's Draft Communications Bill 2002 on the digital television market and the BBC in particular.